PENGARUH PEMBERIAN ALAT PERMAINAN EDUKATIF PADA ANAK USIA TODDLER (1-3 TAHUN) TERHADAP PERKEMBANGAN ANAK DI DESA MOJOWANGIÂ KECAMATANÂ MOJOWARNO KABUPATEN JOMBANGÂ - Ratnaningsih, Tri; Zainuri, Imam (JURNAL KEPERAWATAN SEHAT, 2012)
Currently the community is still found children who can not use age-appropriate games, toddler age children should have been able to use these games so that children can not develop according to his age. Thats why there are still many children who experience delays in the development. The purpose of this study to analyze the Effect of Tool on Childhood Educational Games Toddler (1-3 Years) Against Child Development in the Village District MojowangiMojowarnoJombang District. The method used in this study is an analytical study is an observational analytic, with a "Cross Sectional". Its population is around the toddler age children (1-3 years) in the Village District MojowangiMojowarnoJombang District. Samples in this study were children ages toddler (1-3 years) of 35 children, purposive sampling technique of sampling. Independent variables giving the game an educational tool, the dependent variable of child development. Data obtained by questionnaires and tests disseminate child development at the toddler age children (1-3 years). The results of this study indicate a significant effect by using the Spearman rank test with significance level (0.05) obtained the P value (0.000). These results indicate H0 is rejected, so there is the effect of giving tools to the development of educational games toddler age children (1-3 years). The results of data collection tools available educational games that are not rendered correctly by 16 children (45.71%), child development suspect 12 children (34.29%) and untestable 6 children (17.14%). This is because children are not introduced by means of educational games because of a lack of understanding about the importance of educational toys for child development, children should have educational games so that age-appropriate normal child development.Keywords: Delivery of Equipment Educational Games, Children Ages Toddler (1-3 years), Child Development